Cbfa1 expression in vascular smooth muscle cells may be elevated by increased nitric oxide/iNOS - Maria Aparecida da Gloria; Margaret Gori Mouro; Simone Geraldini; Elisa Mieko Suemitsu Higa; Aluizio Barbosa Carvalho (Brazilian Journal of Nephrology)
ABSTRACT Introduction: Vascular calcification is a common complication of chronic kidney disease. Osteoblast differentiation factor (Cbfa1) is present in histologic sections of arteries from patients with end-stage renal disease. Vascular smooth muscle cells (VSMC) can dedifferentiate to osteoblast-like cells, possibly by up-regulation of Cbfa1. There is evidence that the production of nitric oxide (NO) may have an important role in the regulation of osteoblast metabolism. The aim of this study is to evaluate whether increased NO/iNOS expression causes an increase in cbfa1 expression in VSMC. Methods: VSMC were obtained from renal artery of Wistar male rats, treated for 72 hours with lipopolysaccharide (LPS), ß-glycerophosphate (BGF), a donor of phosphate and aminoguanidine (AG), an inhibitor of iNOS, in the following groups: CTL (control), LPS, BGF, LPS + BGF, and LPS + AG. NO synthesis was determined by chemiluminescence. Cbfa1 and iNOS mRNA expressions were analyzed by RT-PCR, Cbfa1 protein expression by immunohistochemistry and cellular viability by acridine orange. Results: Cbfa1 and iNOS mRNA expressions were higher in LPS and LPS+ BGF vs CTL (p < 0.05), and they were lower in LPS+AG vs LPS (p < 0.05). The Cbfa1 in the groups LPS and LPS+BGF also resulted in a higher value compared to CTL (p < 0.05), and in LPS+AG it was lower compared to LPS (p < 0.05). NO was higher in LPS and LPS+BGF compared to CTL group (p < 0.05) and lower in LPS + AG compared to LPS group (p < 0.05). Cellular viability showed no statistical difference among groups. Conclusion: This study showed that increased NO/iNOS expression causes an increase in cbfa1 expression in VSMC.